2004
DOI: 10.1002/da.20009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic interview assessed neuropsychiatric disorder comorbidity in 334 individuals with obsessive-compulsive disorder

Abstract: Is obsessive-compulsive disorder (OCD) a discrete disorder? Three hundred thirty-four individuals with OCD were interviewed using the Structured Clinical Interview for DSM (SCID). Results demonstrate that OCD is highly comorbid with other neuropsychiatric disorders, with 92% of OCD study participants receiving one or more additional Axis I DSM diagnoses. Among these additional diagnoses, lifetime mood disorders (81%) and anxiety disorders (53%) were the most prevalent. With the exception of substance-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
65
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 78 publications
12
65
0
1
Order By: Relevance
“…High comorbidity between OCD and other anxiety disorders, which was notable in an earlier study in a smaller sample of this cohort of OCD patients (LaSalle et al, 2004), was found in the present study to be significantly associated with both SLC6A4 promotor-region variants, alone and together, with the strongest statistical association being driven by rs25531. Since these two variants interact functionally, this raises the question of whether previous observations of variability in associations between OCD and 5-HTTLPR alone might have been contributed to by different frequencies of comorbid disorders in the diverse OCD populations investigated.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…High comorbidity between OCD and other anxiety disorders, which was notable in an earlier study in a smaller sample of this cohort of OCD patients (LaSalle et al, 2004), was found in the present study to be significantly associated with both SLC6A4 promotor-region variants, alone and together, with the strongest statistical association being driven by rs25531. Since these two variants interact functionally, this raises the question of whether previous observations of variability in associations between OCD and 5-HTTLPR alone might have been contributed to by different frequencies of comorbid disorders in the diverse OCD populations investigated.…”
Section: Discussionsupporting
confidence: 56%
“…Inclusion criteria for participation included being at least 18 years old and having a primary OCD diagnosis based on the Structured Clinical Interview for DSM-IV (SCID). Exclusion criteria included active schizophrenia or psychosis, severe mental retardation that does not permit an evaluation to characterize OCD, or OCD symptoms that occur exclusively in the context of depression (LaSalle et al, 2004). Peripheral blood was collected by venipuncture after written informed consent.…”
Section: Human Subjectsmentioning
confidence: 99%
“…ASD is frequently a co-morbid problem in OCD, both in pediatric (Ivarsson et al, 2007) and in adult populations (LaSalle et al, 2004), at levels that exceeds those that are found in the general population (Ehlers & Gillberg, 1993) (for a review see (Williams et al, 2006)). Also, family members of ASD probands show compulsive personality traits, something that further emphasizes the link between the disorders.…”
mentioning
confidence: 99%
“…7 Further details including rates of comorbidities have been reported elsewhere. 8 MO, USA). As these two groups were not clinically evaluated, we cannot rule out the possibility of individuals present in the control sample with OCD or OC symptoms, although this fraction is unlikely to be higher than the general population prevalence of 2-3%.…”
mentioning
confidence: 99%